2008
DOI: 10.1016/j.abb.2008.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of metal ligand mutants of phenylalanine hydroxylase: Insights into the plasticity of a 2-histidine-1-carboxylate triad

Abstract: The iron atom in the nonheme iron monooxygenase phenylalanine hydroxylase is bound on one face by His285, His290, and Glu330. This arrangement of metal ligands is conserved in the other aromatic amino acid hydroxylases, tyrosine hydroxylase and tryptophan hydroxylase. A similar 2-His-1-carboxylate facial triad of two histidines and an acidic residue are the ligands to the iron in other nonheme iron enzymes, including the α-ketoglutarate dependent hydroxylases and the extradiol dioxygenases. Previous studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Wild-type rat PheH was expressed in E. coli and purified as previously described [24, 25]. The apo-enzyme was reconstituted with ferrous iron under argon immediately before use [16].…”
Section: Methodsmentioning
confidence: 99%
“…Wild-type rat PheH was expressed in E. coli and purified as previously described [24, 25]. The apo-enzyme was reconstituted with ferrous iron under argon immediately before use [16].…”
Section: Methodsmentioning
confidence: 99%
“…Protein Purification and Preparation. The purification of wild-type rat PheH and the catalytic domain (Δ117PheH) were described previously (19,24). To remove the ferric iron present in the enzyme when purified, 45 mL concentrated wild-type PheH (about 2 mg/mL) in 50 mM Hepes, pH 7.0, 15% glycerol, 1 μM pepstatin A, and 1 μM leupeptin was dialyzed overnight against 1 L of the same buffer plus 50 mM EDTA and 50 mM nitrilotriacetic acid (NTA), pH 7.0, with one buffer change.…”
Section: Methodsmentioning
confidence: 99%
“…The ACT domain was an N-terminal regulatory domain to promote allosteric effect, and the Biopterin_H domain was a C-terminal catalytic domain responsible for the conversion from phenylalanine to tyrosine [5,7]. In the Biopterin_H domain of CfPAH, there was a conserved Biopterin-dependent aromatic amino acid hydroxylases signature sequence (from Pro287 to Pro298) with two histidines to bind an iron atom through the form of 2-histidine-1-carboxylate triad [9]. It suggested that CfPAH could possess the similar structure and function to previously reported PAHs.…”
Section: Discussionmentioning
confidence: 99%
“…The homologous catalytic Biopterin_H domains contain an iron-bound motif and a tetramerization motif, and all the residues are required for the determination of substrate specificity and catalytic function [9e11]. For example, the iron is bound to the 2-His-1-carboxylate facial triad constituted by two histidines and an acidic residue in catalytic domain of PAH [9]. PAHs catalyze the reaction from phenylalanine to tyrosine mainly in the liver [12].…”
Section: Introductionmentioning
confidence: 99%